The local impact of centralized irrigation control in Pakistan: a socio-centric perspective - Merrey, Douglas J. (1986)
Reprinted with permission from Lands at Risk in the Third World: Local Level Perspectives, edited by Peter D. Little and Michael M. Horowitz, Boulder, CO, Westview Press, 1986.